Growth hormone deficiency and secondary adrenal insufficiency in petrified ears syndrome: a case report and literature review - Sebastiano Recalcati; Alberto Vassallo; Marta Villanova; Roberto Lanzi; Marco Losa; Maria Grazia Patricelli; Paola Carrera; Fabrizio Fantini (Dermatology Reports)
Petrified ear is a rare clinical entity characterized by the progressive hardening of normal flexible auricular cartilage, leading to partial or complete auricular stiffness. In many cases, it provides a valuable clinical clue that allows the clinician to detect endocrinopathies (particularly Addison’s disease) in a patient who has not received a diagnosis. We present the first documented case of petrified ears, which resulted in the diagnosis of both secondary hypoadrenalism and growth hormone deficiency (GHD). Additionally, we review the relevant literature. Petrified ears syndrome is probably an underreported clinical manifestation of other systemic disorders. It may, at times, serve as a useful and simple clinical clue to suspect underlying endocrinopathies even in the absence of typical features.